2017
DOI: 10.1155/2017/8965729
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Parameters and Hemozoin-Containing Leukocytes and Their Association with Disease Severity among Malaria Infected Children: A Cross-Sectional Study at Pawe General Hospital, Northwest Ethiopia

Abstract: Hematological parameter changes are the most common complications in malaria. We aimed to determine the hematological parameters and hemozoin-containing leukocytes and their association with disease severity in malaria infected children aged between 1 and 15 years. A facility-based cross-sectional study was conducted at Pawe General Hospital from July 31 to December 30, 2014. Demographic and clinical data were collected using structured questionnaire. Blood specimen was collected from each study participant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
4
20
1
Order By: Relevance
“…The AUC was 0.702 and 0.748, sensitivity was 69.0% and 71.05%, and specificity was 70.0% and 72.0% for haemozoincontaining neutrophil and monocytes, respectively. Previous studies have reported a significant association between HCL in children with severe malaria in different African settings [5][6][7][8][9][10][11][12]. The results of our study and these studies should be compared cautiously because of the difference in the malaria endemicity/immunity in the different settings.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The AUC was 0.702 and 0.748, sensitivity was 69.0% and 71.05%, and specificity was 70.0% and 72.0% for haemozoincontaining neutrophil and monocytes, respectively. Previous studies have reported a significant association between HCL in children with severe malaria in different African settings [5][6][7][8][9][10][11][12]. The results of our study and these studies should be compared cautiously because of the difference in the malaria endemicity/immunity in the different settings.…”
Section: Discussionmentioning
confidence: 73%
“…red cell distribution width RDW), mean platelet volume (MPV) and platelet distribution width (PDW) that could be of diagnostic and prognostic value in different diseases including malaria [3,4]. Different blood indices have shown varied cut-off values, sensitivity and specificity in the different settings [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of S1P and S1PR 1 signaling in human malaria has not been investigated in terms of NO production and subsequent clinical outcome. Previous studies investigating the effects of Plasmodium falciparum infections on blood indices show reduction of platelet count (thrombocytopenia) and RBCs (anemia), the two major sources for plasma S1P to be frequent and are responsible for clinical severity with fatal outcome (Birhanu et al, 2017;Punsawad and Viriyavejakul, 2017;Dhangadamajhi et al, 2019). Further, platelet count has been delineated to resolve rapidly with recovery in the absence of any additional and specific treatment (Khan et al, 2012).…”
Section: Human Erythrocytesmentioning
confidence: 99%
“…Circulating and resident monocytes phagocytose and accumulate HZ. The proportion of circulating HZ-containing monocytes increases during malaria (31) and this correlates with disease severity (68). Particularly, HZ-containing monocytes are significantly elevated in patients with SMA (69), and HZ appears to be important in the induction of dyserythropoiesis and apoptosis in nascent erythroid cells (69).…”
Section: Effect Of Malaria Parasites On Monocyte Functionsmentioning
confidence: 99%